1980
DOI: 10.1152/ajprenal.1980.239.5.f420
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of the antiammoniagenic effect of ketone bodies in the dog

Abstract: To investigate the mechanisms of the antiammoniagenic effect of ketone bodies, acidotic dogs (NH4Cl) were infused with either beta-hydroxybutyrate or acetoacetate. Total blood ketones ranged from 2 to 4 mM. Renal ammoniagenesis fell by a mean of 53%, with a proportional decrease in glutamine extraction. Glutamate release in the renal vein rose, renal extraction of lactate fell, and aspartate and alanine production decreased. Study of the metabolite profile of the renal cortex by the freeze-clamp technique befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Metabolism of ketone bodies also sequesters free cardiac coenzyme A as acetoacetyl-CoA, thereby diminishing flux through ·-ketoglutarate dehydrogenase, for which coenzyme A is a reactant [34]. In dog kidney the infusion of either acetoacetate or 3-OH-butyrate markedly increased glutamate production and decreased aspartate output [35].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolism of ketone bodies also sequesters free cardiac coenzyme A as acetoacetyl-CoA, thereby diminishing flux through ·-ketoglutarate dehydrogenase, for which coenzyme A is a reactant [34]. In dog kidney the infusion of either acetoacetate or 3-OH-butyrate markedly increased glutamate production and decreased aspartate output [35].…”
Section: Discussionmentioning
confidence: 99%
“…many hypotheses concerning enhancement of ammoniagenesis during acidosis in dogs consider its concentration as a potential regulator of GDH [4][5][6],…”
Section: Discussionmentioning
confidence: 99%
“…The importance of other pathways for ammoniagenesis in dogs is uncertain [2][3][4], 2-Oxoglutarate occupies an important position in the production of ammonia. Since the GDH is potentially reversible, an accumulation of 2-oxoglutarate by canine kidneys could regulate glutamate ammonia genesis by end-product inhibition [5,6]. In turn, a buildup ofglutamate might then slow the deamidation of glutamine via inhibition of PDG [7,8], Accordingly, a decrease in the Rx renal concentration of 2-oxoglutarate could reverse the chain of events, and augment arnmoniagenesis through GDH and PDG [9], Another possibility exists whereby 2-oxoglutarate buildup controls renal am monia production.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ketone bodies directly inhibit hepatic glucose production, adipocyte lipolysis (Henry et al, 1990), glucose utilization by extrahepatic tissues (Robinson and Williamson, 1980), and glutamine metabolism in the small intestine (Hanson and Parsons, 1978) and kidneys (Lemieux et al, 1980) in mammals. Moreover, in chicken, it has been reported that ketone bodies modulate protein turnover (Wu and Thompson, 1990) and amino acid metabolism (Wu and Thompson, 1988) in the skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%